Kinetika Perubahan Mutu Minyak Buah Merah (Pandanus conoideus) Selama Penyimpanan - Zita Letviany Sarungallo; Budi Santoso; Eduard Fransisco Tethool; Risma Uli Situngkir; Jandri Tupamahu (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Red fruit (Pandanus conoideus) oil contains high unsaturated fatty acids that are readily oxidized during storage, consequently, this affects its quality. Kinetic model can be used to describe the rate of change in quality attributes as a function of time at a certain temperature. This study was aimed to gain kinetic model of quality deterioration of the red fruit oil during storage. Red fruit oil was packaged in dark bottles at a temperature of 60 °C, 75 °C and 90 °C to test their quality stabilities. The water content, free fatty acid (FFA), peroxide value and total carotenoids were observed for ±15 days. The results showed that the quality of the red fruit oil decreases along with the increase of temperature and storage time. The increased levels of free fatty acids and peroxide value of red fruit oil follows the zero order, with Ea value of 43318 J/mol °K and 29437 J/mol °K, respectively. Red fruit oil peroxide value with the lowest Ea showed the most sensitive to oxidative damage during storage. Shelf life estimation of red fruit oil based on the increasing of FFA and peroxide value are following equation of A=Ao-(t.exp[5,6-4.536(1 /T)]) and A=Ao-(t.exp[4,7-3.541(1/T)), respectively. Whereas decrease of carotenoids content follows first order with Ea value was 78,113 J/mol °K. The shelf life estimation for carotenoids content using equation ln A=ln Ao-(t[20,8-9.395(1/T)) ; where A: content of the end; Ao: initial levels; t: storage time (hours); and T: storage temperature (°K). ABSTRAKMinyak buah merah (Pandanus conoideus) mengandung asam lemak tidak jenuh tinggi sehingga mudah teroksidasi dan mempengaruhi mutunya selama penyimpanan. Penelitian ini bertujuan untuk menentukan stabilitas oksidasi minyak buah merah dan mendapatkan model kinetika kerusakan oksidatif mutu minyak buah merah selama penyimpanan pada suhu kritis. Minyak buah merah yang akan diuji stabilitas mutunya dikemas dalam botol gelap pada suhu 60 °C, 75 °C, dan 90 °C, kemudian dilakukan pengamatan terhadap kadar air, kadar asam lemak bebas (ALB), bilangan peroksida dan total karotenoid selama ±15 hari. Hasil penelitian menunjukkan bahwa mutu minyak buah merah menurun dengan meningkatnya suhu dan lama penyimpanan. Peningkatan kadar ALB dan bilangan peroksida minyak buah merah mengikuti orde nol, dengan nilai Ea berturut-turut 37.709 J/mol °K dan 29.437 J/mol °K; sedangkan penurunan kadar karotenoid mengikuti orde 1 dengan nilai Ea 78.113 J/mol °K. Bilangan peroksida minyak buah merah paling sensitif terhadap kerusakan oksidatif selama penyimpanan karena memiliki nilai Ea terendah. Pendugaan umur simpan minyak buah merah berdasarkan kenaikan nilai ALB dan peroksida mengikuti persamaan A=Ao-(t.eksp[5,6-4.536(1 /T)]) dan A=Ao-(t.eksp[4,7-3.541(1/T)). Sementara umur simpan berdasarkan penurunan kadar karotenoid mengikuti persamaan ln A=ln Ao-(t[20,8-9.395(1/T)) dimana A= kadar akhir; Ao= kadar awal; t= lama penyimpanan (jam); dan T= suhu penyimpanan (°K).